Pemeriksaan Kesehatan Tekanan Darah dan Gula Darah di Kelurahan Tamparang Keke Kecamatan Mamajang Kota Makassar - Dirgah Agum Parawansa; Sri Wahyuningsih; Marhawati Marhawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension and diabetes mellitus are chronic diseases that are often not detected early due to the lack of public attention to health checks. Both diseases are known as “silent killers” because they often go unnoticed until they cause serious complications. Health screening activities were carried out in Tamparang Keke Village, Mamajang Subdistrict, Makassar City, focusing on blood pressure and blood sugar levels. Of the 27 residents examined, 8 had hypertension, 1 hypotension, and 8 had high blood sugar levels. It is recommended that residents regularly check their health, adopt a healthy diet, and exercise to reduce the risk of complications.